2021
DOI: 10.3389/fvets.2021.641441
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Equine Allogeneic Tenogenic Primed Mesenchymal Stem Cells in a Surgically Induced Superficial Digital Flexor Tendon Lesion Model

Abstract: Background: Tendon injuries are very common in horses and jeopardize the athletic performance, and due to the high risk of reinjury may lead to early retirement. The use of mesenchymal stem cells for the treatment of equine tendon disease is widely investigated because of their regenerative potential. The objective of this study is to investigate the safety and efficacy of equine allogeneic tenogenic primed mesenchymal stem cells (tpMSCs) for the management of tendinitis in horses.Methods: A core lesion was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
1
20
0
1
Order By: Relevance
“…Based on current results, it remains unclear whether this could be related to the presence of a naturally occurring equine sarcoid in one sero-converting horse or if it is an individual non-specific immune response against one or several different (xeno)antigens. Despite the occurrence of the non-specific immune response in one horse, a previous study performed by our group including these horses revealed no clinical abnormalities and promising results of the tpMSC treatment ( 46 ). Owens et al, reported an anti-BM-MSC antibody response in 37% of the horses receiving an allogeneic treatment ( 15 ).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Based on current results, it remains unclear whether this could be related to the presence of a naturally occurring equine sarcoid in one sero-converting horse or if it is an individual non-specific immune response against one or several different (xeno)antigens. Despite the occurrence of the non-specific immune response in one horse, a previous study performed by our group including these horses revealed no clinical abnormalities and promising results of the tpMSC treatment ( 46 ). Owens et al, reported an anti-BM-MSC antibody response in 37% of the horses receiving an allogeneic treatment ( 15 ).…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, in clinical studies, the allogeneic use of MSCs has been described for single ( 12 , 23 , 46 ) and repeated ( 24 , 25 ) treatment of horses suffering from tendon injuries without evidence of any local immunological reactions (absence of heat, swelling, pain or lameness) after intralesional injection. On the other hand, a higher number of circulating CD8 T-cells after repeated intravenous injection of equine allogeneic MSCs has been reported ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each assessment, a complete examination of the SDFT was conducted by means of longitudinal and transverse scans. The obtained images were evaluated and scored (from 0 to 3) at each examination for two parameters as previously described (24,39): lesion echogenicity and lesion longitudinal fiber alignment (FA). Criteria for scoring are listed in Table 1.…”
Section: Diagnostic Imaging: Ultrasound Evaluationmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) derived from multiple sources, as bone marrow (BM-MSCs), adipose tissue (AD-MSCs), or peripheral blood (PB-MSCs), have proved their efficacy in improving tendon healing in horses thus reducing the reoccurrence rate of injury, mainly because of their paracrine activity (21)(22)(23)(24). Different route of administration of MSCs, including intralesional injection, have demonstrated to be a safe and effective practice to treat tendon injury in equine medicine (25,26).…”
Section: Introductionmentioning
confidence: 99%